Technology-Assisted Pronunciation: Using Elsa Speak Application To Master –Ed Endings - Septa Aryanika; Nava Anggri Safitri; M. Ridho Kholid; Ernando Rizki Dalimunte (Yayasan Darussalam Bengkulu, 2025)
Many students face difficulties in pronouncing –ed endings, especially in distinguishing /t/, /d/, and /ɪd/ sounds, which affects their speaking skills. This study aimed to improve students’ pronunciation through the use of the ELSA Speak application. Using Classroom Action Research (Kemmis & McTaggart) with two cycles, the research involved 32 seventh-grade students of SMPN 1 Candipuro in the 2024/2025 academic year. Data were collected through observation, pre-tests, and post-tests, and analyzed quantitatively and qualitatively.Results showed a significant improvement in pronunciation, with the average score rising from 56.25 (pre-test) to 72.81 (cycle I) and 83.28 (cycle II). Students also gained more confidence and motivation. In conclusion, ELSA Speak effectively enhanced students’ mastery of –ed endings and is recommended as a digital tool in English learning.